2002
DOI: 10.1002/art.10221
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term risk of mortality and lymphoproliferative disease and predictive classification of primary Sjögren's syndrome

Abstract: Objective. Primary Sjögren's syndrome (SS) may lead to lymphoproliferative disease (LPD) and death in certain patients. We sought to determine the incidence and predictors of adverse long-term outcomes to achieve a rational predictive classification of the syndrome.Methods. Predictive modeling was performed in a cohort of 723 consecutive patients with primary SS (587 newly diagnosed [incident] cases and 136 prevalent cases).Results. During 4,384 person-years of followup, we recorded 39 deaths (7 due to lymphom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

15
268
2
18

Year Published

2004
2004
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 434 publications
(306 citation statements)
references
References 20 publications
15
268
2
18
Order By: Relevance
“…Thus, we support the proposal by Ioannidis and coworkers that patients with primary SS can be classified into type 1 and 2 as early as at the time of diagnosis (11). This spares the majority of patients (ϳ75%) from worry about premature death.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Thus, we support the proposal by Ioannidis and coworkers that patients with primary SS can be classified into type 1 and 2 as early as at the time of diagnosis (11). This spares the majority of patients (ϳ75%) from worry about premature death.…”
Section: Discussionsupporting
confidence: 91%
“…In addition, we found that a low C3 level (Յ0.83 gm/liter) at diagnosis was a predictor of death, mainly due to lymphoproliferative disease. This tendency was also seen in the Greek study, but was not significant in that study (11). The main explanation for the difference between the studies could be the different cutoff levels for C3: 0.50 gm/liter in the Greek study versus 0.83 gm/liter in ours, while the cutoff levels for low C4 were the same in the 2 studies.…”
Section: Discussionmentioning
confidence: 48%
See 2 more Smart Citations
“…Although many studies have focused on the risk of neoplasia in SS [10][11][12][13][14], we found only four publications in which acute leukaemia was cited ( Table 1) [15][16][17][18]. The first publication reported on a 59-year-old woman with primary SS diagnosed in 1963.…”
Section: Literature Reviewmentioning
confidence: 99%